2019
DOI: 10.1038/s41380-019-0622-y
|View full text |Cite
|
Sign up to set email alerts
|

Cellular calcium in bipolar disorder: systematic review and meta-analysis

Abstract: Calcium signalling has long been implicated in bipolar disorder, especially by reports of altered intracellular calcium ion concentrations ([Ca 2+ ]). However, the evidence has not been appraised critically. We carried out a systematic review and metaanalysis of studies of cellular calcium indices in bipolar disorder. 2281 records were identified and 117 screened, of which 32 were eligible and 21 were suitable for meta-analyses. The latter each involved up to 642 patients and 404 control subjects. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 81 publications
(98 reference statements)
2
44
0
2
Order By: Relevance
“…Among the molecular pathways related to BD, calcium signaling has been highlighted [62,63], supporting previous findings on aberrant calcium signaling in BD [64,65]. In addition, a recent meta-analysis showed that there is a robust increase of basal and stimulated free intracellular calcium in BD [66], reinforcing the role of impaired calcium signaling in this illness. A chronic accumulation of calcium could be associated with cellular dysfunctions and the aforementioned impaired cellular resilience in BD.…”
Section: Impaired Calcium Signalingsupporting
confidence: 63%
“…Among the molecular pathways related to BD, calcium signaling has been highlighted [62,63], supporting previous findings on aberrant calcium signaling in BD [64,65]. In addition, a recent meta-analysis showed that there is a robust increase of basal and stimulated free intracellular calcium in BD [66], reinforcing the role of impaired calcium signaling in this illness. A chronic accumulation of calcium could be associated with cellular dysfunctions and the aforementioned impaired cellular resilience in BD.…”
Section: Impaired Calcium Signalingsupporting
confidence: 63%
“…Calcium signaling is involved in neuroplasticity induced by BDNF and glutamatergic mechanisms [ 214 , 215 , 216 ]. The relationship between changes in the concentration of mitochondrial or intracellular calcium and the development of depressive disorders has been demonstrated [ 19 , 217 , 218 ].…”
Section: Contribution Of Sigma1r Chaperone To the Molecular Mechanmentioning
confidence: 99%
“…The role of glutamatergic processes in the development of depressive disorders and rapid antidepressant action has been confirmed experimentally [ 15 , 16 , 17 ]. The importance of potassium channels, intracellular calcium, and post-receptor signaling pathways has been demonstrated [ 18 , 19 , 20 ]. In the 1990s, sigma-1 receptors (Sigma1R) were considered as a pharmacological target for antidepressants.…”
Section: Introductionmentioning
confidence: 99%
“…adenylate cyclase and phosphodiesterases (Lane Brown et al 2006), may also be involved in the pathogenesis of postpartum mood disorders. Abnormal calcium signalling, phosphodiesterase activity, and cyclic AMP/GMP signalling have been implicated in a variety of neurological and psychiatric (mood) conditions (Hebb and Robertson 2007;Harrison et al 2019), with much focus on phosphodiesterase 10A (PDE10A). PDE10A is highly expressed in the GABAergic neurons of the olfactory tubercle and the striatum (MacMullen et al 2017), is dysregulated in an animal model of postpartum depression (Yun et al 2019), and has been genetically associated with bipolar disorder, hypo-and hyperthyroidism, and blood pressure (GWAS Catalog 2020).…”
Section: Conclusion and Future Research Avenuesmentioning
confidence: 99%